Histopathologic spectrum of psoriasis - Kaddu, S... (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 1999)
The many clinical faces of psoriasis are reflected by the spectrum of histopathologic changes ranging from guttate psoriasis to generalized pustularpsoriasis. Psoriasis is a dynamic process and consequently the morphologic changes vary during the evolution and subsequent resolution of theindividual lesions. For example, a fully developed psoriatic lesion revealspsoriasiform acanthosis of the epidermis characterized by elongated thin or club shaped rete ridges of equal length alternating with thin dermal papillae that are covered by thin suprapapillary plates. Typically, there is confluent parakeratosis, which contains accumulation of neutrophils. The granular layer is decreased or absent. In the upper part of the dermis there is a moderately dense perivascular and interstitial infiltrate of lymphocytes in association with dilated spiraled capillaries in the dermal papillae and marked edema of the papillary dermis. Besides early, fully developed and late lesions of "classical" psoriasis, palmoplantar psoriasis, pustular psoriasis and erythrodermic psoriasis are all characterized by distinctive morphologic changes that, in many instances, allow a histopathologic diagnosis with certainty. The most important differential diagnoses from a histopathologic point of view are as follows: psoriasiform trichophytia, pityriasis rubra pilaris, pityriasis rosea, nummular dermatitis, chronic contact dermatitis, lichen simplex chronicus and rupial syphilis. In conclusion, the histopathologic findings of the many faces of psoriasis are distinctive and allow a definitive diagnosis by the experienced dermatopathologist in nearly all instances. Until today no laboratory methods including modern molecular technologies are replacing conventional histopathology in the diagnosis of psoriasis.
Keywords: Keratinocytes; Pathology; Psoriasis